Key competencies for psychedelic treatment in real-world mental health care settings - Wolff, Max; Rutrecht, Hans; Gründer, Gerhard; Jungaberle, Andrea; Jungaberle, Henrik (General hospital psychiatry, 2025)
Psychedelic treatments are extending beyond research units and into hospitals, outpatient clinics, and community practices. Contrasting the constrained procedures of clinical trials with the realities of routine practice, this article outlines the competencies needed for safe, effective, and ethically sound psychedelic therapy in everyday mental health care. To accommodate mainstream adoption of these treatments, the competencies framework we present respects the distinctive contextual and cultural sensitivities of psychedelic care while remaining anchored in established psychotherapeutic, medical, and scientific paradigms. Designed for varied service models, the framework is substance-unspecific (i.e., covering various classical and atypical psychedelic agents) and transtheoretical (i.e., compatible with cognitive-behavioral, psychodynamic, humanistic-experiential, systemic and other psychotherapeutic orientations). Developed within the MIND Foundation's Augmented Psychotherapy Training (APT) program, the framework spans foundational psychotherapeutic, biomedical, philosophical, socio-cultural, existential, legal, and self-experiential domains and translates them into practical competencies for multi-professional cooperation, screening, preparation, dosing, integration, and harm-reduction. While the framework awaits systematic evaluation across diverse clinical contexts, it offers an initial blueprint for future accredited certification pathways and for the ongoing refinement of clinician training as these treatments enter mainstream care.